The impact of collectivism orientation and gender identity on work-life balance and life satisfaction relationship: a UK – Spain comparison - Valero Pizarro, Irene; Arman, Gamze (Journal of Management and Business Education, 2021)
Difficulties in balancing work and non-work roles have a negative impact on an individual’s life satisfaction. This study investigates the relationship between work-life balance and life satisfaction across the United Kingdom and Spain. It also explores the moderating effects of individual orientations of collectivism and gender identity. The used scales measured Work-life Balance (WLB), Life Satisfaction (LS), Collectivism vs. Individualism orientations, and Gender identity. Collectivism/Individualism was measured and analysed at individual-level rather than at cultural-level. Data was collected from 52 British and 69 Spanish full-time employed women through an online survey. Correlational analyses and hierarchical multiple regression were conducted. Findings indicated that work-life balance had positive effects on life satisfaction across two different cultures. Those effects were stronger for British than Spanish women. Moderating effects were not found. Although, work-life balance, collectivism individual-orientation, and feminine identity predicted life satisfaction in the UK and only work-life balance predicted life satisfaction in Spain. This study extends the literature on work-life balance and life satisfaction relationship and the influence of culture, whilst also contributing to the under-researched area of the influence of gender identity on that relationship. The results might contribute to developing better strategies for promoting work-life balance